Answer:
23 times 12 times 2= 552. but i dont understand the last part so think there is a typo
Step-by-step explanation:
Answer:
We have expanded formula of (-4x-1)² = a²+2ab+b².
So, we write the formula in square form as (a+b)².
Since we have a²-b² in step 4. We further write this as (a+b)(a-b). This is the factor formula of a²-b².
As we had two terms in place of in (a+b)(a-b), we multiply the term 'b' with '+' and '-' sign respectively.
Write the second expression given in the question.
Write the terms in the form of cube.
Write the factor formula of a³-b³) in the form of (a-b)(a²+ab+b²).
Write the H.C.F. (Highest Common Factor) of the given expressions by analysing the factors you generated in each expressions. Here, (4x²+2x+1) are the common factors.
Answer:
let x = 0
therefore
24=4(0)+6y
24=0+6y
24=6y
y= 24/6
y=4
you can take different value of x and the value of y will change automatically
Answer:
Answer:
15% off 212.5
30% off 175$
Step-by-step explanation:
15+15=30 so
250/100=2.5
2.5x30=75
250-75